(3Ydi LfGM OQGLI (B=s On a bicycle wing : (3ef WfLI Edi HGQjS (B/s - (3HdMGL, YGFTIs ((3CHhXHj (B- (3GdEeGQGJ GdYQHjI GdeJMOI (B:s (3OGQ GdShjOj ddfTQ hGdJhRjY ,s (3HjQhJ (B- (3dHfGf (B:s (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ ,s (3YeGf (B- (3GdCQOf (B:s (3OGQ GdaGQS ddfTQ hGdJhRjY ,s, 2023)
(3JJejR gPg GdQMdI HdZJgG GdTjbI GdJj JUa HgG HGQjS, eaSMI GdeLGd ddSaQ GdacQj hGdJCedj HGQjS, HGdfSHI EdjgG, gj Gdaf hGdCOH hGdeSQM hGdSjfeG, hgj GdacQ ZjQ GdJbdjOj hGdKhQI Ydi GdYGOGJ GdHGdjI, hGdfRhY Edi GdMQjI GdaQOjI(B. (3dbO MVQJ GdcGJHI Edi HGQjS HPGcQI KbGajI LGgRI dJCed GdCecfI HYjf eNJdaI haQjOI, GMJTOJ ajgG YfGhjf GdcJH hGdehVhYGJ GdJj GNJRdJgG GdPGcQI Yf YGUeI GdCfhGQ, ef bQGAGJgG dcJH cKjQI SHb hSGaQJ Edi HGQjS hajgG hYHQgG, aef WfLI Edi HGQjS MedJ GdcGJHI JhbkG TOjOkG ddhbha Ydi eG GSJbHdJg ef Jdc GdUhQ hGdeYGde hGdeTGgO HYjf SjfeGFjI CfKhjI(B.s
(3GdcJGH GdMGFR Ydi LGFRI GHf HWhWI aQY GdQMdI GdeYGUQI (B2022-2023s
(3JUeje GdZdGa (B: (3fGUQ HNjJ ; NWhW GdZdGa (B: (3eMeO fLjH HQHhQ ; GdUa GdVhFj (B: (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ(B.s
Keywords: (3GdeacQGJ GdCOHjIs -- (3ePcQGJs -- (3jhejGJs -- (3bQf (B21s; (3HGQjS (B((3aQfSG(B)s -- (3hUa hQMdGJs -- (3eQhjGJ TNUjIs; (3WfLI (B((3GdeZQH(B)s -- (3hUa hQMdGJs -- (3eQhjGJ TNUjIs